Nutritional, Antioxidant and Glycemic Response of Dark Chocolate Prepared with Sacha Inchi Oil - Halib, Hasmiza; Rozaimi, Nurul Syafiqah; Awi, Anis Sofiya; Taib, Nur Anis Syafiqah; Hussin, Napisah; Mhd Jalil, Abbe Maleyki; Saupi, Intan Anis (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study aimed to enhance the nutritional and functional quality of dark chocolate by incorporating Sacha Inchi Oil (SIO), a healthier fat alternative derived from Plukenetia volubilis, which is rich in polyunsaturated fatty acids and antioxidants. The potential of SIO as a Cocoa Butter Equivalent (CBE) was evaluated in dark chocolate formulations containing 1%, 3%, and 5% SIO. Proximate composition and antioxidant capacity were analysed using standard methods (soxhlet, kjeldahl, total polyphenol content, total flavonoid content, 2,2-diphenyl-1-picrylhydrazyl (DPPH), and FRAP). Significant differences (p<0.05) were observed in fat, fiber, moisture, and energy contents, with the 5% SIO formulation showing reduced fat and energy levels, increased fiber and moisture, and the highest antioxidant activity. Additionally, a non-randomized controlled trial involving ten healthy participants was conducted to determine the Glycemic Index (GI) and Glycemic Load (GL) of the samples. While the control and 1% SIO samples exhibited high GI, the 3% and 5% SIO formulations were classified as medium GI, and all samples demonstrated low GL. The 5% SIO chocolate had the lowest glycemic response. These findings indicate that SIO can improve the nutritional profile, antioxidant properties, and glycemic response of dark chocolate, supporting its application as a functional ingredient in the development of healthier chocolate products, particularly for health-conscious populations in developing countries.